Life Expectancy, Fertility, and Women's Lives: A Life-History Perspective. (May 2013) - Low, Bobbi S.; Parker, Nicholas; Hazel, Ashley; Welch, Kathleen B.
Women's reproductive lives vary considerably around the world, yet there are patterns to this variation. We explore reproductive patterns in 177 nations using the framework of human behavioral ecology. In humans, as in other species, there is a normally strong relationship between life expectancy at birth (e0 ) and age at first birth (AFB). However, in studies of nonhuman species, this relationship is subject to two implicit assumptions: (a) that any population will be representative of the species, demonstrably untrue for humans (Low et al., 2008), and (b) that the relationship between e0 and AFB is at equilibrium. What happens if, as is common in humans, changes occur rapidly in life expectancy? Here we explore the factors influencing how patterns of female life expectancy at birth (e0 ) have changed since 1955. We examine the world's worst-off countries (in which e0 did not predict AFB) to see what predicts life expectancy, age at first birth, and total fertility rate (TFR), and discuss how these features of human biocultural diversity may have policy implications for women's fertility and societal roles.